Guidance And Counseling In Junior High School (SMP) And High School (SMA) - Nina Milaturokhah; Muhammad Yoga Nugraha (P3M STAI Kuningan, 2023)
This study aims to describe Guidance and Counseling (BK) held in Junior High School (SMP) and Senior High School (SMA). The results showed: (1) Junior High School (SMP), (2) Senior High School (SMA), (3) guidance and counseling, (4) material and equipment for secondary school guidance and counseling. Guidance and counseling students are expected to understand to realize the goals of guidance and counseling optimally.